Dual Redox Reaction Sites for Pseudocapacitance Based on Ti and −P Functional Groups of Ti3C2PBrx MXene - Zhu, Jiamin; Zhu, Shengli; Cui, Zhenduo; Li, Zhaoyang; Wu, Shuilin; Xu, Wence; Gao, Zhonghui; Ba, Te; Liang, Chunyong; Liang, Yanqin; Jiang, Hui (Angewandte Chemie, 2024)
MXenes have extensive applications due to their different properties determined by intrinsic structures and various functional groups. Exploring different functional groups of MXenes leads to improved performance or potential applications. In this work, we prepared new Ti3C2PBrx (x=0.4–0.6) MXene with phosphorus functional groups (−P) through a two‐step gas‐phase reaction. The acquisition of −P is achieved by replacing bromine functional groups (−Br) of Ti3C2Br2 in the phosphorus vapor. After −Br is replaced with −P, Ti3C2PBrx MXene shows an improved areal capacitance (360 mF cm−2) at 20 mV s−1 compared with Ti3C2Br2 MXene (102 mF cm−2). At a current density of 5 mA cm−2 after 10000 cycles, the capacitance retention of Ti3C2PBrx MXene has not decreased. The pseudocapacitive enhancement mechanism has been discovered based on the dual redox sites of the functional groups −P and Ti. MXene with phosphorus functional groups (−P) has been prepared by replacing −Br in Ti3C2Br2 with gas‐phase P. Ti3C2PBrx (x=0.4–0.6) powder is directly obtained and the atomic content of P reaches the theoretical atomic percentage content. Compared to MXene Ti3C2Br2 with the −Br functional groups, the areal capacitance of Ti3C2PBrx with −P functional groups has increased by about 3.6 times at scan rates of 20 mV s−1, and the capacitance retention rate has not decreased after 10000 cycles. The pseudocapacitive enhancement mechanism has been discovered based on the dual redox sites of the functional groups −P and Ti.